2009
DOI: 10.1002/jts.20464
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance and baroreceptor sensitivity in women with posttraumatic stress disorder

Abstract: In a previous study, women with posttraumatic stress disorder (PTSD) had greater objective sleep disturbance than those without. In a separate previous study, women with PTSD were also found to have lower baroreceptor sensitivity (BRS), an index of blood pressure regulation. In the present study, we concurrently assessed BRS and objective sleep by diagnostic status. Comparison of 32 women with PTSD to 21 women without PTSD revealed an interaction between BRS and sleep efficiency, Wake after Sleep Onset percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…A PTSD diagnosis involves hyperarousal, re-experiencing of stress and sleep difficulties 25 , and having a diagnosis of PTSD places one at greater risk of hypertension 26 and death due to early onset of coronary heart disease 27 . In a sample of women, we found evidence of these shared associations across several previous studies, including one study focused on baroreceptor sensitivity 28 . Baroreceptors are sensors located in the wall of blood vessels which detect blood pressure changes and relay this information to the central nervous system.…”
Section: Introductionsupporting
confidence: 64%
“…A PTSD diagnosis involves hyperarousal, re-experiencing of stress and sleep difficulties 25 , and having a diagnosis of PTSD places one at greater risk of hypertension 26 and death due to early onset of coronary heart disease 27 . In a sample of women, we found evidence of these shared associations across several previous studies, including one study focused on baroreceptor sensitivity 28 . Baroreceptors are sensors located in the wall of blood vessels which detect blood pressure changes and relay this information to the central nervous system.…”
Section: Introductionsupporting
confidence: 64%
“…Furthermore, while baroreceptor sensitivity decreased for all participants during an anger recall task, the change was less dramatic for women with PTSD, possibly due to their lower resting values (76). More recently, in a study of women with and without PTSD, an interaction was detected between baroreceptor sensitivity and objective sleep parameters (79). Lower baroreceptor sensitivity was associated with poorer sleep in women with PTSD, but not in those without PTSD (79).…”
Section: Biomarkers Of Cardiovascular and Metabolic Disease In Ptsdmentioning
confidence: 99%
“…More recently, in a study of women with and without PTSD, an interaction was detected between baroreceptor sensitivity and objective sleep parameters (79). Lower baroreceptor sensitivity was associated with poorer sleep in women with PTSD, but not in those without PTSD (79). …”
Section: Biomarkers Of Cardiovascular and Metabolic Disease In Ptsdmentioning
confidence: 99%
“…For example, individuals with PTSD have increased prevalence of blood pressure dysregulation (6-8). Although results from previous studies have been mixed, meta-analyses have demonstrated that PTSD is associated with elevations in resting systolic and diastolic blood pressure (9, 10).…”
Section: Introductionmentioning
confidence: 99%